The future of bariatric surgery research: A worldwide mapping of registered trials. (17th February 2022) - Rives‐Lange, Claire; Poghosyan, Tigran; Rassy, Nathalie; Carette, Claire; Phan, Aurelie; Goeau‐Brissonnière, Marc; de Castelbajac, Flore; Merazka, Amel; Czernichow, Sebastien
Summary: The bariatric surgery (BS) research landscape is a continuous evolving. Since the first described procedure, numerous different techniques have been developed by surgical teams. In this context, we conducted a systematic mapping of upcoming randomized controlled trials (RCTs) in BS for people with obesity. In June 2021, we performed a systematic review of RCTs evaluating BS versus another surgical procedure or versus a medical control group, through a search in ClinicalTrials.gov . There was no restriction on outcomes for study selection. A total of 62 RCTs were included, totaling 10, 800 potential individuals to be included, with planned Roux‐en‐Y gastric bypass (RYGB) and sleeve gastrectomy surgeries the most common. The median number of patients planned to be enrolled is 78 (IQR: 50–143). Mean follow‐up time is 12 months in 55% of trials and 4 years or more in 23%. The most frequent (81% of RCTs) outcomes to be investigated are obesity‐related diseases with the study of type 2 diabetes, followed by weight loss, quality of life, and surgical complications. The rising number of BS procedures around the world has been followed by a subsequent surge in BS research. An increase in interest is observed in outcomes such as obesity‐related diseases, intermediate metabolic markers, quality of life, and body composition.